Human capital development for global competitiveness : defining priorities and articulating strategies - Benn, Denis (2005)
Seeks to identify the nature and content of human capital development and its role in enabling the Caribbean to compete effectively in a rapidly changing global environment shaped by the twin forces of globalisation and economic liberalization.
A publication of the UWI-CARICOM Project